Theoretical and Applied Aspects of the Categorical and Conceptual Apparatus of Legal Psychology - V.D. Balin; V.A. Ilyina (Психология и право, 2023)
The article reflects the results of a study of theoretical and applied aspects of the categori-cal and conceptual apparatus of legal psychology from a critical point of view. Conclusions are drawn about the special position of legal psychology as an applied discipline in relation to the legal sciences, in connection with which the priority role in solving its problems is given to legal concepts, which in their essence are self-sufficient and conventional. The conventional nature of legal concepts, built on an agreement between lawyers in the under-standing of certain terms, comes down to the fact that in their content they in some cases do not coincide with the content of general psychological categories and concepts. In terms of scope, they are either narrower or wider than psychological concepts. In this regard, the significant reverse influence of psychological concepts on legal ones, expressed in the re-flection of psychological patterns and mechanisms of psychological and legal phenomena, becomes a laborious and long process, since legal concepts do not aim to reflect the true structure of the world. The features of the categorical-conceptual apparatus of legal psy-chology listed in this study make it possible to more accurately determine the direction of scientific research, correctly understand the needs of legal practice and predict the long-term consequences of the results of one’s scientific activity.